2016
DOI: 10.15561/18189172.2016.0207
|View full text |Cite
|
Sign up to set email alerts
|

Peculiar features of men physical condition in planning highly intensive physical loads in winter period

Abstract: Abstract. Physical functioning of average and high intensity is an important component of mature men's health and longevity. For highly intensive physical functioning organism's physical fitness is required. Human physical condition can change under influence of season factors. Purpose: to determine specific features of men's physical condition before their highly intensive physical trainings in winter period and test them. Material: 25 men of 35-48 years' age without chronic diseases were chosen for experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Pryshva O.B. [8] confirmed that determination of athletes' adaptation potential and its dynamic shall be considered in trainings' planning and assessment of training effectiveness. The similar results were received also in other works [9,10].…”
Section: Introductionmentioning
confidence: 85%
“…Pryshva O.B. [8] confirmed that determination of athletes' adaptation potential and its dynamic shall be considered in trainings' planning and assessment of training effectiveness. The similar results were received also in other works [9,10].…”
Section: Introductionmentioning
confidence: 85%
“…In this case correct and careful teaching of advantages and safety of recommended physical functioning can replace false ideas and fears of elderly people about risks, connected with physical exercises. It can rise their motivation for regular physical functioning (Bertoldo Benedetti et al, 2011;D'Amico et al, 2015;Pop, 2016;Pryshva, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It is also explained by CVS activation the next day [3,17], when API confidently grows. Such energy accumulation results in natural demand in HIPA.…”
Section: Discussionmentioning
confidence: 99%
“…But mature man's organism is not always ready for such intensity. In researches [2,3] we found dependence of men's highly intensive physical activity (HIPA) on CVS current condition. It served as indicator of human general physical condition at the beginning of training day, which, probably, is conditioned by life style the day before.…”
mentioning
confidence: 99%